MOTIVASI PEDAGANG BERJUALAN DI LOKASI OBYEK WISATA ISTANA SIAK, KABUPATEN SIAK - ", Buiman; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of Kampung In districts Siak Siak district with the aim to, among others: To find out how motivated traders to sell around the site a tourist attraction Siak Palace. To determine the relationship trader with fellow traders who are planted in the Palace of Siak attractions.This research is descriptive kauatitatif, with respondents traders around the site a tourist attraction Siak Palace. The data collection techniques by using questionnaires, observation, and documentation on asedental sampling of respondents coincidence that exist in the field. To analyze the data obtained by researchers using quantitative descriptive method Based on these results, we can conclude that the motivation behind the traders who sell at the site of the Palace tourist attraction Siak Siak district is a strategic place, visitors are crowded, and to promote local products. While the relationship among traders in the tourist locations Siak Palace is very good.Keywords: Motivation Dealer, Tourism Object Siak Palace.